THE ENCHANTMENT OF FREIREAN PEDAGOGY - Utta, Bergson (2022)
In this work we reflect on the experiences of Paulo Freire, socialized in the books “Letters to Cristina: reflections on my life and my praxis” and “Fear and daring: the teacher's daily life”, which show the constituent bases of the enchantment of Freire's pedagogy. Paulo Freire's history with education is worthy of reflection, as his praxis led him to idealize a popular education that aimed to raise awareness among people, especially the oppressed and excluded social classes, with a view to social, cultural and political emancipation, the which in itself is an indication of his belief in the liberating power of education. From the reading of these works, we will use as a methodology to analyze their experiences, the five-dimensionality of González (2008) with a focus on the five dimensions (methodological, epistemological, ontological, axiological and teleological) proposed by him. In addition to Freire (2008, 2019 and 2021), scholars of the patron of Brazilian education such as Haddad (2019) and Gadotti (2011), add to this reflection. This study showed us that Freire's life and experiences reinforce the constituent bases of his ideation and, based on them, through a critical treatment, he gave his pedagogy political and epistemological recognition, evidencing the enchantment of his pedagogy.